Math, asked by singhutkarshaman, 6 months ago

X + 2/6-(11-X/3-1/4)=3x-4/12

Answers

Answered by harshitha926594
0

Step-by-step explanation:

 \frac{x + 2}{6}  - ( \frac{11 - x}{3}  -  \frac{1}{4} ) =  \frac{3x - 4}{12} \\ \frac{x + 2}{6}  - ( \frac{4(11 - x)}{12}  -  \frac{3(1)}{12} ) =  \frac{3x - 4}{12}\\ \frac{x + 2}{6}   - ( \frac{44 - 4x - 3}{12} ) =  \frac{3x - 4}{12}  \\  \frac{x  + 2}{6}  -  (\frac{41 - 4x}{12} ) =  \frac{3x - 4}{12}  \\  \frac{2(x  + 2)}{12}  -  (\frac{41 - 4x}{12} ) =  \frac{3x - 4}{12} \\  \frac{2x  + 4 - 41 + 4x}{12}  =  \frac{3x - 4}{12}  \\  \frac{6x - 37}{12}  =  \frac{3x - 4}{12}  \\ 12(6x - 37) = 12(3x - 4) \\ 72x-444 = 36x-48 \\ 72x-36x = -48+444 \\ 36x=396\\ x =  \frac{396}{36}  \\ \underline{\underline {x = 11}}

Answered by Salmonpanna2022
0

Step-by-step explanation:

\mathsf{Given : \dfrac{x + 2}{6} - \bigg(\dfrac{11 - x}{3} - \dfrac{1}{4}\bigg) = \dfrac{3x - 4}{12}}

\mathsf{\implies \dfrac{x + 2}{6} - \bigg(\dfrac{4(11 - x) - 3}{12}\bigg) = \dfrac{3x - 4}{12}}

\mathsf{\implies \dfrac{x + 2}{6} - \bigg(\dfrac{44 - 4x - 3}{12}\bigg) = \dfrac{3x - 4}{12}}

\mathsf{\implies \dfrac{x + 2}{6} - \bigg(\dfrac{41 - 4x}{12}\bigg) = \dfrac{3x - 4}{12}}

\mathsf{\implies \bigg(\dfrac{x + 2}{6} - \dfrac{(41 - 4x)}{12}\bigg) = \dfrac{3x - 4}{12}}

\mathsf{\implies \dfrac{2(x + 2) - (41 - 4x)}{12} = \dfrac{3x - 4}{12}}

\mathsf{\implies \dfrac{2x + 4 - 41 + 4x}{12} = \dfrac{3x - 4}{12}}

\mathsf{\implies \dfrac{-37 + 6x}{12} = \dfrac{3x - 4}{12}}

\mathsf{\implies {-37 + 6x} = {3x - 4}}

\mathsf{\implies 6x - 3x = 37 - 4}

\mathsf{\implies 3x = 33}

\mathsf{\implies x = \dfrac{33}{3}}

\mathsf{\implies x = 11}

Similar questions